Internacionalização de empresas em redes horizontais: uma análise a partir do Projeto Setorial Integrado Wines from Brazil - Dalmoro, Marlon (2009)
Internationalization strategies and networks associations are becoming a way face the new global situation. In order to better understand the internationalization process, considering interorganizational relationships in networks, this study aims to describe and analyze the internationalization processes of companies in interorganizational networks of horizontal character in order to understand how the relationships in these networks influence the penetration of associated companies in the international market. In theory mark, it was deepening the internationalization process theory in industrial networks. At the epistemological level, was given a qualitative approach through a case study. The unit of analysis is the Integrated Sector Project Wines from Brazil, formed by 34 companies in the wine industry and maintained by the Brazilian Institute of Wine - IBRAVIN with the support of APEX Brasil. It appears that the project has the characteristics of an interorganizational network, arranged in a horizontal form, which develops international activities with the characteristics of an export consortium. Data were collected through semi-structured interviews, conducted in situ with 14 managers of associated companies and two managers of the network under investigation, complementing with observation and analysis of documents. Data were analyzed using the content analysis technique with the help of the conceptual matrix. Overall, it appears that the network association forms an environment propitious to internationalization process, especially for smaller companies linked to the network. It was concluded that the Integrated Sector Project Wines from Brazil serves as a tool to help overcome the barriers of internationalization. View to cooperation in the network as a result of the need for companies to seek new markets to overcome the difficulties of the internal market. The globalization process creates a learning network as a whole and the connections of the network generate learning for businesses and the internationalization process. This knowledge generation provided by the network, result in organizational learning and regional learning. The project is crucial to the business internationalization, cooperation between participating organizations and the support given by the project have allowed an increasing number of wineries Brazilian companies active in the international market.